Antifungal, Antileishmanial, and Cytotoxicity Activities of Various Extracts of Berberis vulgaris (Berberidaceae) and Its Active Principle Berberine. (10th March 2014) - Mahmoudvand, Hossein; Ayatollahi Mousavi, Seyyed Amin; Sepahvand, Asghar; Sharififar, Fariba; Ezatpour, Behrouz; Gorohi, Fatemeh; Saedi Dezaki, Ebrahim; Jahanbakhsh, Sareh
Abstract : In this study, in vitro antidermatophytic activity against Trichophyton mentagrophytes, Trichophyton rubrum, Microsporum canis, and Microsporum gypseum was studied by disk diffusion test and assessment of minimum inhibitory concentration (MIC) using CLSI broth macrodilution method (M38-A2). Moreover, antileishmanial and cytotoxicity activity of B. vulgaris and berberine against promastigotes of Leishmania major and Leishmania tropica were evaluated by colorimetric MTT assay. The findings indicated that the various extracts of B. vulgaris particularly berberine showed high potential antidermatophytic against pathogenic dermatophytes tested with MIC values varying from 0.125 to >4 mg/mL. The results revealed that B. vulgaris extracts as well as berberine were effective in inhibiting L. major and L. tropica promastigotes growth in a dose-dependent manner with IC50 (50% inhibitory concentration) values varying from 2.1 to 26.6  μ g/mL. Moreover, it could be observed that berberine as compared with B. vulgaris exhibited more cytotoxicity against murine macrophages with CC50 (cytotoxicity concentration for 50% of cells) values varying from 27.3 to 362.6  μ g/mL. Results of this investigation were the first step in the search for new antidermatophytic and antileishmanial drugs. However, further works are required to evaluate exact effect of these extracts in animal models as well as volunteer human subjects.